Social contract: a critical study of its development - Gough,J. W. (London, 1957)
When the book first appeared, some critics said that it was too much concerned with theory, and did not pay enough attention to the actual events and situations which gave rise to the theory. This is a criticism to which any history of thought must be liable to some degree. Perhaps the most serious risk in writing the history of an idea is that by following its appearances in a succession of writers, especially when each writer admits his indebtedness by quotations from and references to his predecessors, one may give an appearance of continuity which is really misleading.
Keywords: Sociology